Abundance estimates of three cetacean species in the coastal waters of Matang, Perak, Peninsular Malaysia. Issue 11 (6th September 2021) - Kuit, Sui Hyang; Ponnampalam, Louisa Shobhini; Hammond, Philip S.; Chong, Ving Ching; Then, Amy Yee‐Hui
Abstract: The paucity of baseline data on coastal cetaceans due to a lack of research in developing countries frequently precludes assessment of their status and informed management actions for conservation. This study provides the first abundance estimates of Indo‐Pacific humpback dolphins, Irrawaddy dolphins, and Indo‐Pacific finless porpoises in the coastal waters of Matang, Peninsular Malaysia. Boat‐based surveys covering 1, 152 km 2 of coastal waters with 4, 108 km of survey effort were conducted between 2013 and 2016 to collect data for line transect analysis of Irrawaddy dolphins and finless porpoises. Photo‐identification data of humpback dolphins were concurrently collected for mark–recapture analysis. Estimates of abundance from four sampling strata totalled 763 Irrawaddy dolphins ( CV  = 13%, 95% confidence interval (CI) [588, 990]) and 600 Indo‐Pacific finless porpoises ( CV  = 27%, 95% CI [354, 1, 016]). The annual abundance estimates of humpback dolphins ranged between 171 (95% CI [148, 208]) in 2014–2015 and 81 (95% CI [67, 98]) in 2015–2016, likely due to the presence of offshore individuals that moved in and out of the study area. The estuarine strata were inhabited by 68 (95% CI [63, 73]) inshore humpback dolphins in 2013–2014 to 87 (95% CI [78, 97]) dolphins in 2014–2015. As an International Union for Conservation of Nature important marine mammal area, the productive coastal waters of Matang are shown to support a high density of small coastal cetaceans, and the results serve as an important baseline for future studies to identify population trends for conservation management plans.